Harmoni Alam dan Spiritualitas: Studi Kepercayaan Orang Manggarai Timur terhadap Roh Alam - Gole, Hendrikus; Sudhiarsa, Raymundus I Made (Sahabat Publikasi, 2024)
The focus of this study discusses natural damage as negative changes in the natural environment, especially as a result of human activities. Air, water, and soil pollution, as well as climate change are the main elements that contribute to the destruction of nature, threaten the sustainability of ecosystems and cause biodiversity loss with negative impacts on human health. This study aims to explore the belief of Manggarai people in nature spirits. In their belief, nature spirits are considered the guardians of the balance of the ecosystem, and every element of nature is inhabited by spirits possessing spiritual power. The destruction of nature is seen as a disturbance to the spirit of nature, creating disharmony in the ecosystem and the potential for natural disasters. The study highlights the importance of not only maintaining physical ecosystems but also maintaining spiritual balance with the spirits of nature. This study uses literature methods sourced from books and scientific articles that are in accordance with this discourse. The results of this study provide deep insight into the belief system of the East Manggarai people towards nature spirits. This study found that the relationship between nature and humans is the essence of human life. Man cannot live without nature. Nature becomes a container to provide life for humans.